Implementasi Undang-Undang Informasi dan Transaksi Elektronik terhadap Kasus Penipuan Online di Provinsi Lampung - Dheva Cloddea Sadli (Jurnal Hukum Lex Generalis, 2025)
Online fraud has increased significantly and caused losses to the community, including in Lampung Province. This study aims to analyze the implementation of the Electronic Information and Transaction Law in cases of online fraud in Lampung Province and the obstacles encountered. The research method used is normative juridical with a legislative approach that examines the provisions of the ITE Law, the Criminal Code, and other laws and regulations. The results of the study show that the implementation of the ITE Law in handling online fraud cases in Lampung Province has a sufficient legal basis, particularly through Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the ITE Law and the provisions of Article 378 of the Criminal Code. Therefore, cross- institutional coordination should be optimized, and the role of local governments and community participation should be enhanced to realize legal protection for victims of online fraud.